PENGARUH GREEN INTELLECTUAL CAPITAL TERHADAP KINERJA LINGKUNGAN PERAN MEDIASI GREEN HUMAN RESOURCE MANAGEMENT PADA HOTEL - Farida, Florentina Anif; Purwanto, Agus (JURNAL EKOBIS DEWANTARA, 2025)
The hotel pays attention to the environment as a form of the hotel's responsi-bility and concern for the environment. The aim of this research is to examine the effect of green intellectual capital on environmental performance mediat-ed by environmentally friendly human resource management of star hotels in Madiun. The approach in this research uses a quantitative approach. The research sample consisted of 60 respondents, the measuring instrument used was a questionnaire with a Likert scale. This research analysis uses the Part Least Square (PLS) measurement approach version 3.0. The research results show that green intellectual capital has a significant positive effect on envi-ronmental performance. Green Intellectual Capital has a positive and signifi-cant effect on environmentally friendly human resource management. Green Human Resource Management has a significant positive effect on hotel envi-ronmental performance. Green Intellectual Capital has a positive and signifi-cant effect on the environmental performance of star hotels in Madiun which is partially mediated by Green Human Resource Management.